Konsep Dasar Dan Desain Pengembangan Kurikulum PAI - Achmad Junaedi Sitika; Alfa Briyan Nudin; Ayuning Nurul Khasanah; Cucu Darojatun Ajria; Dinda Nurul Azkiya; Fathur Rahman (Jurnal Ilmiah Wahana Pendidikan, 2023)
Islamic Religious Education (PAI) curriculum development is a complex process that involves various elements such as objectives, materials, activities, and evaluation. Islamic education curriculum development is important to create better teaching and learning conditions and meet the needs of students and society. In developing the PAI curriculum, the underlying principles such as the concept of Islam, the First Precepts of Pancasila, the 1945 Constitution, and the Law on the National Education System serve as guidelines. There are three main designs used in the development of the PAI curriculum, namely SCD, LCD, PCD, and SFD. Each design has its own advantages and disadvantages, and it is important for the curriculum designer to choose a design that fits the needs and goals of teaching PAI.